Organizational Culture, Social Capital, Financial Literacy, and SME Performance in Coastal Economy: Evidence from Kenjeran, Indonesia - Fatmawati, Rini; Prihatiningtyas, Setya; Hartati Setyowarni, Sri (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study examines the effects of organizational culture, social capital, managerial capability, and financial literacy on SME performance in coastal economic settings, with evidence from Kenjeran, Surabaya, Indonesia. Despite extensive research on SME performance, prior studies remain fragmented and predominantly focus on urban and formal sectors, limiting understanding of how intangible resources operate in informal and coastal environments. Using a quantitative approach, data were collected from 60 seafood processing SMEs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that financial literacy, managerial capability, and social capital have significant positive effects on SME performance, while organizational culture does not have a significant effect. These findings indicate that the effectiveness of intangible resources is context dependent, where relational and capability-based resources, particularly social capital, play a more dominant role than formal organizational structures in coastal SMEs. This study contributes to the refinement of the resource-based view by demonstrating that not all intangible resources have equal relevance across different contexts. From a practical perspective, the findings suggest that policies aimed at improving SME performance in coastal areas should prioritize strengthening social networks, enhancing financial capability, and supporting adaptive managerial practices in informal economic environments.